(untitled) (Mediscope, 2021)
Background: Congenital heart disease (CHD) has already been recognized as one of the important cause of neonatal mortality and morbidity. The reported prevalence of CHD in live newborns tends to vary a lot due to various unrecognizable lesions at birth and lack of technical expertise. Aims & objectives: The ultimate aim of this study was to assess the birth incidence and pattern of congenital heart disease (CHD) using echocardiography in babies born in different government and private hospitals and also in different households. Results: Overall incidence of congenital heart disease in neonate in this study was 4.9 per 1000 live birth. Mean age of diagnosis was 22.5±4.6 days. Average weight of these neonates was 26.70 gm. 61.5 % neonates were female. 30.8% was preterm. Respiratory distress was the most common clinical presentation (76.9%). The commonest type of congenital heart disease was Ventricular septal defect (VSD) (61.5%). Maternal co-morbidity may have influence. 30.8% mothers had gestational diabetes mellitus. Hypothyroidism, hypertension and maternal infection may have co-relation. Conclusion: In this study, we have found that the overall incidence of neonatal congenital heart disease is 4.9 per 1000 live birth. A high index of suspicion and routine neonatal cheek-up may have key role in diagnosis. Mediscope Vol. 8, No. 1: January 2021, Page 27-32